Designing of precise vaccine construct against visceral leishmaniasis through predicted epitope ensemble: A contemporary approach. (June 2020) - Singh, Garima; Pritam, Manisha; Banerjee, Monisha; Singh, Akhilesh Kumar; Singh, Satarudra Prakash
Graphical abstract: Highlights: Systematic prediction of B- and T-cell epitopes sourced from Leishmania donovani antigens. Designing of monomeric vaccine constructs using suitable linkers to enhance their antigen processing and presentation ability. Evaluation of vaccine constructs based on molecular docking and immune simulation studies. Abstract: Visceral leishmaniasis (VL) caused by Leishmania donovani is a fatal parasitic disease affecting primarily the poor population in endemic countries. Increasing number of deaths as well as resistant to existing drugs necessitates the development of an effective vaccine for successful treatment of VL. The present study employed a combinatorial approach for designing monomer vaccine construct against L. donovani by applying forecasted B- and T- cell epitopes from 4 genome derived antigenic proteins having secretory signal peptides and glycophosphatidylinositol (GPI) anchors with ≤ 1 transmembrane helix. The forecasted population coverage of chosen T cell epitope ensemble (combined HLA class I and II) cover 99.14 % of world-wide human population. The predicted 3D structure of vaccine constructs (VC1/VC2) were modeled using homology modeling approach and docked to innate immune receptors TLR-2 and TLR-4 with respective docking energies −1231.4/−910.3 and −1119.4/−1476 kcal/mol. Overall, the aforementioned designed vaccine constructs were found appropriate for including in self-assembly protein nanoparticles (SAPN) for further study in developing cutting-edge precision vaccine against VL in short duration with cost-effective manner.